Effectiveness of Using Cad (Computer-Aided Design) Through the Richpeace Digital Application Program in Grading Clothing Patterns in the Fashion Design Education Study Program PKK FT Unimed - Nababan, Chintya Mei Sony; Daulay, Kania Salsabilah; Simorangkir, Rindu; Halawa, Silvia Rosalina; Hutajulu, Ribka R.; Sidabalok, Rincawani; Farihah, Farihah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The fashion industry is rapidly evolving with the support of digital technologies such as Computer-Aided Design (CAD). This study evaluates the effectiveness of using the Richpeace Digital application in garment pattern grading among students of the Fashion Education Study Program at the Faculty of Engineering, State University of Medan. The method employed is a quantitative pre-experimental design with two groups: an experimental group using the CAD application and a control group using manual methods. Data were collected through questionnaires, interviews, and documentation. The results show that the use of Richpeace Digital increased the speed of grading pattern completion by up to 50% compared to manual methods dditionally, the accuracy of the patterns improved significantly with a reduction in measurement errors. Reliability testing yielded a Cronbach’s Alpha value above 0.90, indicating highly reliable instruments, while normality tests showed normally distributed data. Simple linear regression analysis revealed a positive, albeit weak (R = 0.155), relationship between basic computer skills and the effectiveness of CAD application use. The application also significantly enhanced students' technical skills and motivated their interest in digital pattern grading. This study recommends integrating the Richpeace. An abstranct is a brief summary of a research article, thesis, review, conference  proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry  for any given academic  paper or patent application.  Absatrcting  and indexing services for various  academic  discipline  are aimed  at compiling  a body of literature  for that  particular  subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.